2016
DOI: 10.2340/00015555-2249
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lamellar Bodies are not Discrete Vesicles but Part of a Tubuloreticular Network

Abstract: Improved knowledge of the topology of lamellar bodies is a prerequisite for a molecular-level understanding of skin barrier formation, which in turn may provide clues as to the underlying causes of barrier-deficient skin disease. The aim of this study was to examine the key question of continuity vs. discreteness of the lamellar body system using 3 highly specialized and complementary 3-dimensional (3D) electron microscopy methodologies; tomography of vitreous sections (TOVIS), freeze-substitution serial secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Next to a tough and resilient organization of the flattened corneocytes, the envelope of proteins and lipids surrounding each corneocyte also plays a crucial role in preventing the penetration and diffusion of foreign substances through the skin and loss of internal water. The currently accepted model of the SC, although subject to change [5,6,7], also contains the intercellular lipid lamellae, a product originating from the lamellar bodies of the stratum granulosum, and consisting of ceramides, fatty acids, and cholesterol. Located between the corneocytes, it contributes to the overall skin barrier function [3,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Next to a tough and resilient organization of the flattened corneocytes, the envelope of proteins and lipids surrounding each corneocyte also plays a crucial role in preventing the penetration and diffusion of foreign substances through the skin and loss of internal water. The currently accepted model of the SC, although subject to change [5,6,7], also contains the intercellular lipid lamellae, a product originating from the lamellar bodies of the stratum granulosum, and consisting of ceramides, fatty acids, and cholesterol. Located between the corneocytes, it contributes to the overall skin barrier function [3,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of extensive electron microscopy studies, Landmann described epidermal lamellar bodies as ovoid, membrane‐delimited and lamellate organelles measuring ∼200 nm in diameter . However, recent studies conducted by Norlen's group suggested that the lamellar body system is composed of a single and coherent tuboreticular membrane network . In both models, the presence of stacked lamellar structures seems to be relevant, although these lamellar structures are packed into discrete vesicles in the Landmann model and into a tubuloreticular membrane system in the Norlen model.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal lamellar bodies are produced in the stratum granulosum by keratinocytes, and secrete their contents – precursors of the stratum corneum lipids, hydrolases, protease inhibitors, and antimicrobial peptides – into the intercellular space at the stratum granulosum–stratum corneum interface to form the lamellar structure of this tissue . Two models have been proposed for skin barrier formation: the Landmann model, which proposes that lamellar bodies are discrete vesicles ; and the membrane‐folding model, which proposes that lamellar bodies form part of a tubuloreticular membrane network .…”
mentioning
confidence: 99%
“…CYP4F22 belongs to the key players of epidermal lipid metabolism involved in the formation of the permeability barrier, some components of which have already been identified, in particular regarding lamellar bodies; CLE and intercorneal lipid lamellae; and, at the next lower level, enzymes involved in acylceramide formation, processing and cross‐linking to proteins of the CLE, i.e. FATP4, ELOV1/4, CYP4F22, CERS3, ABCA12, ALOX12B/ALOXE3 and TGM1.…”
mentioning
confidence: 99%